The Meaning of Symbols in Nunas nede Ritual Tradition in Kesik Village - Husna, Mardiatul; Mari’i; Muh. Syahrul Qodri (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Nunas nede is a cultural ritual inherited from the ancestors of Kesik Village, Masbagik District, East Lombok. The nunas nede tradition is believed to be an expression of a request for rain and gratitude for the blessings of fertile agricultural land and harvests that have been given to the people of Kesik Village. The nunas nede tradition consists of two core activities, namely ngayu ayu and gawe adat (core event). Each procession in the Nunas nede tradition is a symbol of the beliefs of the people of Kesik Village. These symbols describe the meaning in the Nunas nede tradition. This research was conducted to analyze the meaning of the Nunas nede tradition using Clifford Geertz's symbolic interpretive theory. There are three concepts in Geertz's theory, namely the knowledge or cognitive system (mode of), the value or evaluative system (mode for); and (3) symbol system. These three concepts will produce a system of meaning from the nunas nede tradition. The results of the research show that the symbols in the nunas nede tradition are the begibung symbol meaning establishing ties of friendship and social equality in society, the dulang symbol meaning gratitude, the nyawik symbol meaning maintaining the balance of nature and the spring symbol meaning the source of life. From these symbols, the meaning of the nunas nede tradition is obtained, a request for rain to fall as well as a form of community gratitude which is a link between friendship and strengthening family ties, by working together to maintain the balance of the universe which is the source of life.